2015
DOI: 10.1016/j.immuni.2015.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Action of STAT Transcription Factors Drives Transcriptional Outputs and Cytokine Specificity

Abstract: Interleukin-6 (IL-6) and IL-27 signal through a shared receptor subunit and employ the same downstream STAT transcription proteins, but yet are ascribed unique and overlapping functions. To evaluate the specificity and redundancy for these cytokines, we quantified their global transcriptomic changes and determined the relative contributions of STAT1 and STAT3 using genetic models and chromatin immunoprecipitation-sequencing (ChIP-seq) approaches. We found an extensive overlap of the transcriptomes induced by I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
140
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(143 citation statements)
references
References 53 publications
3
140
0
Order By: Relevance
“…Surprisingly lack of STAT1 has a totally different impact in murine CD4+ activated T cells in their study. It leads to a drastic increase in commonly regulated genes by those two cytokines meaning that this transcription factor confers the differences in gene induction between the two cytokines [30]. These and other data show that for example priming of cells with IFN-g or gain of function mutations in STAT1 would result in an altered IL-27 response and increased distinction compared to an IL-6 response [31].…”
Section: Signal Transduction and Cross-talk Of Il-27mentioning
confidence: 77%
“…Surprisingly lack of STAT1 has a totally different impact in murine CD4+ activated T cells in their study. It leads to a drastic increase in commonly regulated genes by those two cytokines meaning that this transcription factor confers the differences in gene induction between the two cytokines [30]. These and other data show that for example priming of cells with IFN-g or gain of function mutations in STAT1 would result in an altered IL-27 response and increased distinction compared to an IL-6 response [31].…”
Section: Signal Transduction and Cross-talk Of Il-27mentioning
confidence: 77%
“…Previous studies have suggested that IL-27-induced STAT1 and STAT3 make distinct contributions to the transcriptional output. While STAT3 deficiency is associated with loss of the overall cytokine response, the major function of STAT1 is to provide specificity 27 . We found that IRF1 is expressed downstream of STAT1, while BATF expression is STAT3-dependent, which might account for some of the transcriptional differences observed between STAT1 and STAT3 deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…An altered balance between STAT1 and STAT3 was observed in T cells of patients with STAT1 GOF mutations stimulated with IL-6 and IL-27, suggesting that analogous mechanisms involving STAT1 and STAT5 might explain the observed IL2RA upregulation in IL-15-stimulated NK cells of patients with STAT1 GOF mutation. 40 In patients with CMCD, STAT1 GOF mutations are associated with a characteristic delay of protein dephosphorylation, resulting in persistent activation of the signaling pathway. 5,18,24,25 In our study the time course analysis of STAT1 phosphorylation in response to IFN-a has shown a similar pattern in NK cells of patients with STAT1 GOF mutations.…”
Section: Discussionmentioning
confidence: 99%